Maintenance of acute stroke care service during the COVID-19 pandemic lockdown - Altersberger, Valerian L.; Stolze, Lotte J.; Heldner, Mirjam R.; Henon, Hilde; Martinez-Majander, Nicolas; Hametner, Christian; Nordanstig, Annika; Zini, Andrea; Nannoni, Stefania; Gonçalves, Bruno; Nolte, Christian H.; Baumgartner, Philipp; et al. (Stroke, 2021)
Download figureDownload PowerPoint